Effect of foam filling on the energy absorption behaviour of flax/polylactic acid composite interlocking sandwich structures. (15th July 2022) - Alsubari, S.; Zuhri, M.Y.M.; Sapuan, S.M.; Ishak, M.R.
Abstract: A novel double cell wall interlocking square core was fabricated from flax fibre reinforced polylactic acid composite. Initially, a series of square core panels with cell sizes of 20, 30, and 40 mm were manufactured using hot press machine and later fabricated using a simple slotting technique. Then, series of quasi-static compression test loadings with a crosshead displacement rate of 2 mm/min were carried out on empty and filled-foam core structure with different densities. Here, the effect of using double cell walls, different cell sizes and foam-filled core structure were investigated. Based on the results, the compressive strength and specific energy absorption (SEA) increased by up to 3.45–126% and 3.75–64% with respect to empty core structure. It was also demonstrated that the higher the foam density filled in a smaller cell size core structure, the greater the effect on its strength and SEA. In addition, the variation of the cell core sizes was more pronounced in the case of the empty core structure compared to their foam-filled core counterparts. Finally, the current results were found to be between 7 and 10 times higher than those of single cell walls reported in the literature in terms of their strength and SEA.